Environmental and water, sanitation and hygiene conditions in schools: a community-based cross-sectional study from North India - Aniruddh, Ranga; J. P., Majra (International Journal of Research in Medical Sciences, 2021)
Background: Schools environment is essential for children to achieve optimal health and development. Faulty construction leads to inadequate ventilation and moisture accumulation which increase the levels of morbidities. Schools should also serve as demonstration centres of good sanitation to the community hence healthful environment and functional toilets and WASH facilities are of utmost importance for school children. Methods: A community-based cross-sectional study includes randomly selected 50 schools of Sonepat district which were functional for more than 5 years. Schools were recruited by PPS. A schedule was used to assess the environment and WASH conditions. Percentage, proportion and Chi-square test were used as statistical methods. The p-value <0.05 was considered statistically significant. Results: 68.4% government schools and 51.6% private schools were located in a rural area. 68% schools were having multi-storied building, 72% schools were located at appropriate land. Ventilation was inadequate in 58% schools while all schools were having adequate lighting. Ergonomically sitting facilities were observed in one school only. Water treatment was done in 68% schools. Toilets were adequate in 58% schools but cleaning was done daily in 46% schools. Handwashing points were available in 96% schools but soap was observed in 10.4% schools only. Garbage disposal was observed to be sanitary in 52% schools while liquid waste disposal was sanitary in 44% schools. Conclusions: The study points towards deficiency of environment and WASH conditions in schools and recommends the school authorities to take corrective measures.